Preparation method of asymmetric capacitor carbon material coated positive electrode material
Patent Information
- Application Number
- CN202310563388.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-18
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-05-18
AI Technical Summary
[0004]传统认为在大电流密度下,影响MO//C非对称电容器的循环寿命受到正极材料的影响,但随着电流密度的增加,通过对正极的改性来提高MO//C非对称电容器的循环寿命的收益在逐渐减小
[0018]This invention involves soaking carbon materials in concentrated acid to remove impurities. The treated carbon materials are then added to an electrolyte as an electrodeposition solution. Through electrodeposition, the carbon materials are coated onto the surface of the positive electrode material, reducing the shedding of the positive electrode material during cycling. This inhibits the deposition of the negative electrode in the supercapacitor and improves the electrochemical performance of the supercapacitor.
Smart Images

Figure CN116435114B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of supercapacitor technology, and in particular to a method for suppressing negative electrode deposition. Background Technology
[0002] Asymmetric capacitors composed of metal oxides and carbon materials (MO / / C) can improve energy density without sacrificing power density and cycle stability, demonstrating promising performance in high-power energy storage and energy transmission applications. Developing energy storage devices with high specific energy, high power density, and long cycle life has always been a key research direction in the energy storage field. Batteries, as common energy storage devices, can improve specific energy, but modern electronic devices place significantly higher demands on battery power density. Supercapacitors offer high power density, but their relatively low energy density limits their applications in many areas. MO / / C asymmetric capacitors inherit the advantages of both while avoiding their disadvantages, showing promising application prospects.
[0003] Currently, global automation and electronification pose new challenges to the high-current cycling capabilities of asymmetric capacitors. MO / / C asymmetric capacitors have certain limitations in their high-current carrying capacity; as current density increases, the cycle life of MO / / C asymmetric capacitors shows an accelerated decline.
[0004] Traditionally, it's believed that the cycle life of MO / / C asymmetric capacitors at high current densities is influenced by the cathode material. However, as current density increases, the benefit of modifying the cathode to improve the cycle life of MO / / C asymmetric capacitors gradually diminishes. Furthermore, when the current density increases to a certain level, elemental metal deposition occurs on the anode. This deposition on the anode surface causes a decrease in the original active potential of the anode, leading to a sharp reduction in capacitance. This deposition intensifies with increasing current density. Therefore, suppressing elemental metal deposition on the anode surface is a key strategy for improving the cycle life of MO / / C asymmetric capacitors at high current densities.
[0005] For the deposition of elemental metals on the negative electrode to occur, two conditions must be met: 1) the ions reduced from the positive electrode can move smoothly to the surface of the negative electrode; 2) the voltage applied to the negative electrode is negative than the voltage at which metal ions are deposited. Therefore, reducing the movement of reduced ions from the positive electrode to the surface of the negative electrode is a way to suppress the deposition of elemental metals on the negative electrode at its source, thereby improving the cycle life of supercapacitors. Summary of the Invention
[0006] The purpose of this invention is to provide a method for suppressing the electrodeposition of the positive electrode onto the negative electrode, thereby improving the cycle life of supercapacitors. To achieve the above-mentioned objective, the technical solution provided by this invention is as follows:
[0007] A method for preparing a carbon-coated cathode material for an asymmetric capacitor includes the following steps:
[0008] 1) The carbon material is placed in concentrated acid for stirring and cleaning, centrifuged, washed with water and alcohol in sequence, and then dried in an oven; the carbon material is one of single-walled carbon nanotubes, multi-walled carbon nanotubes, and graphene.
[0009] 2) Add the treated carbon material to the electrolyte for mixing; the electrolyte is one of KOH solution or NaOH solution with a concentration of 1~6 mol / L.
[0010] 3) Using the electrolyte treated in step 2) as the electrodeposition solution, copper foam as the working electrode and platinum sheet as the counter electrode, carbon-coated copper hydroxide is prepared by electrodeposition. The electrodeposition method is constant current deposition. The conditions for constant current deposition are: current of 10~30mA and electrodeposition time of 20~60min.
[0011] 4) The electrode material obtained in step 3) is placed in a tube furnace for calcination to prepare carbon-coated copper oxide, i.e., the carbon-coated positive electrode material; the calcination temperature is 150~300℃, the calcination time is 2~4h, and the heating rate is 2~5℃ / min.
[0012] Preferably, the concentrated acid mentioned in step 1) is one of concentrated hydrochloric acid and concentrated nitric acid;
[0013] Preferably, in step 1), the concentrated acid washing and stirring time is 20-60 min; the centrifugation speed is 4000-8000 r / min; and the centrifugation time is 3-8 min.
[0014] Preferably, the electrolyte in step 2) has a concentration of 3 mol / L.
[0015] Preferably, in step 2), the mixing method involves simultaneous stirring and ultrasonic treatment; the stirring and ultrasonic treatment time is 30-60 min, more preferably 30 min; and the ultrasonic power is 240-360 W, more preferably 360 W.
[0016] Preferably, in step 3), the calcination temperature of the tube furnace is 200℃; the calcination time is 3h; and the heating rate of the tube furnace is 3℃ / min.
[0017] The beneficial effects of this invention are:
[0018] This invention involves soaking carbon materials in concentrated acid to remove impurities. The treated carbon materials are then added to an electrolyte as an electrodeposition solution. Through electrodeposition, the carbon materials are coated onto the surface of the positive electrode material, reducing the shedding of the positive electrode material during cycling. This inhibits the deposition of the negative electrode in the supercapacitor and improves the electrochemical performance of the supercapacitor.
[0019] The method of this invention only requires treating the carbon material with concentrated acid, mixing it with an electrolyte, and then using a one-step electrodeposition method to coat the carbon material onto the surface of the cathode material. This method is simple to operate, convenient, low in cost, and easy to implement for industrial-scale mass production. Attached Figure Description
[0020] Figure 1 A schematic diagram of the preparation process of this invention.
[0021] Figure 2 Example 1: SEM image of copper oxide material coated with multi-walled carbon nanotubes prepared by constant current deposition.
[0022] Figure 3 SEM image of the negative electrode after comparative cyclic testing;
[0023] Figure 4 SEM image of the negative electrode after cycle testing in Example 1. Detailed Implementation
[0024] The following detailed description, in conjunction with embodiments, illustrates the method for suppressing the deposition of the negative electrode in a supercapacitor by coating the positive electrode material with carbon material according to the present invention. However, this should not be construed as limiting the scope of protection of the present invention.
[0025] Example 1
[0026] (1) Add 50 mL of 95% concentrated nitric acid to a 100 mL beaker, weigh 100 mg of multi-walled carbon nanotubes and add them to the concentrated nitric acid. Stir for 30 minutes. After stirring, centrifuge, wash once with water and once with alcohol, and then take out the multi-walled carbon nanotubes and put them in an oven at 60 °C to dry for 10 h to obtain dried single-walled carbon nanotubes.
[0027] (2) Weigh 50 mg of the above multi-walled carbon nanotubes and add them to 50 mL of 3M potassium hydroxide solution. Stir for 30 minutes and then sonicate for 30 minutes to ensure that the multi-walled carbon nanotubes and potassium hydroxide solution are fully mixed.
[0028] (3) Using copper foam as the working electrode and platinum sheet as the counter electrode, constant current electrodeposition was performed in the above mixed solution. The current was 10 mA and the deposition time was 30 min. Copper hydroxide material coated with multi-walled carbon nanotubes was obtained.
[0029] (4) The copper hydroxide material coated with multi-walled carbon nanotubes was placed in a tube furnace for calcination. The reaction temperature was controlled at 200℃, the heating rate was adjusted to 2℃ / min, and the temperature was maintained for calcination for 3h. After the reaction was completed, copper oxide material coated with multi-walled carbon nanotubes was obtained.
[0030] (5) The copper oxide material coated with multi-walled carbon nanotubes was used as the positive electrode material to assemble a supercapacitor and the electrochemical performance was tested.
[0031] Example 2
[0032] (1) Add 50 mL of 95% concentrated nitric acid to a 100 mL beaker, weigh 100 mg of multi-walled carbon nanotubes and add them to the concentrated nitric acid. Stir for 30 minutes. After stirring, centrifuge, wash once with water and once with alcohol, and then take out the multi-walled carbon nanotubes and put them in an oven at 60 °C to dry for 10 h to obtain dried single-walled carbon nanotubes.
[0033] (2) Weigh 40 mg of the above multi-walled carbon nanotubes and add them to 50 mL of 3M potassium hydroxide solution. Stir for 30 minutes and then sonicate for 30 minutes to ensure that the multi-walled carbon nanotubes and potassium hydroxide solution are fully mixed.
[0034] (3) Using copper foam as the working electrode and platinum sheet as the counter electrode, constant current electrodeposition was performed in the above mixed solution. The current was 10 mA and the deposition time was 30 min. Copper hydroxide material coated with multi-walled carbon nanotubes was obtained.
[0035] (4) The copper hydroxide material coated with multi-walled carbon nanotubes was placed in a tube furnace for calcination. The reaction temperature was controlled at 200℃, the heating rate was adjusted to 2℃ / min, and the temperature was maintained for calcination for 3h. After the reaction was completed, copper oxide material coated with multi-walled carbon nanotubes was obtained.
[0036] (5) The copper oxide material coated with multi-walled carbon nanotubes was used as the positive electrode material to assemble a supercapacitor and the electrochemical performance was tested.
[0037] Example 3
[0038] (1) Add 50 mL of 95% concentrated nitric acid to a 100 mL beaker, weigh 100 mg of multi-walled carbon nanotubes and add them to the concentrated nitric acid. Stir for 30 minutes. After stirring, centrifuge, wash once with water and once with alcohol, and then take out the multi-walled carbon nanotubes and put them in an oven at 60 °C to dry for 10 h to obtain dried single-walled carbon nanotubes.
[0039] (2) Weigh 60 mg of the above multi-walled carbon nanotubes and add them to 50 mL of 3M potassium hydroxide solution. Stir for 30 minutes and then sonicate for 30 minutes to ensure that the multi-walled carbon nanotubes and potassium hydroxide solution are fully mixed.
[0040] (3) Using copper foam as the working electrode and platinum sheet as the counter electrode, constant current electrodeposition was performed in the above mixed solution. The current was 10 mA and the deposition time was 30 min. Copper hydroxide material coated with multi-walled carbon nanotubes was obtained.
[0041] (4) The copper hydroxide material coated with multi-walled carbon nanotubes was placed in a tube furnace for calcination. The reaction temperature was controlled at 200℃, the heating rate was adjusted to 2℃ / min, and the temperature was maintained for calcination for 3h. After the reaction was completed, copper oxide material coated with multi-walled carbon nanotubes was obtained.
[0042] (5) The copper oxide material coated with multi-walled carbon nanotubes was used as the positive electrode material to assemble a supercapacitor and the electrochemical performance was tested.
[0043] Example 4
[0044] (1) Add 50 mL of 95% concentrated nitric acid to a 100 mL beaker, weigh 100 mg of multi-walled carbon nanotubes and add them to the concentrated nitric acid. Stir for 30 minutes. After stirring, centrifuge, wash once with water and once with alcohol, and then take out the multi-walled carbon nanotubes and put them in an oven at 60 °C to dry for 10 h to obtain dried single-walled carbon nanotubes.
[0045] (2) Weigh 70 mg of the above-mentioned multi-walled carbon nanotubes and add them to 50 mL of 3M potassium hydroxide solution. Stir for 30 minutes and then sonicate for 30 minutes to ensure that the multi-walled carbon nanotubes and potassium hydroxide solution are fully mixed.
[0046] (3) Using copper foam as the working electrode and platinum sheet as the counter electrode, constant current electrodeposition was performed in the above mixed solution. The current was 10 mA and the deposition time was 30 min. Copper hydroxide material coated with multi-walled carbon nanotubes was obtained.
[0047] (4) The copper hydroxide material coated with multi-walled carbon nanotubes was placed in a tube furnace for calcination. The reaction temperature was controlled at 200℃, the heating rate was adjusted to 2℃ / min, and the temperature was maintained for calcination for 3h. After the reaction was completed, copper oxide material coated with multi-walled carbon nanotubes was obtained.
[0048] (5) The copper oxide material coated with multi-walled carbon nanotubes was used as the positive electrode material to assemble a supercapacitor and the electrochemical performance was tested.
[0049] Comparative Example 1
[0050] Electrodeposition was performed using the same method, but without the addition of carbon materials.
[0051] (1) Using copper foam as the working electrode and a platinum sheet as the counter electrode, constant current electrodeposition was performed in the above 3M potassium hydroxide solution. The current was 10mA and the deposition time was 30min. Copper hydroxide material was obtained.
[0052] (2) The obtained copper hydroxide material was placed in a tube furnace for calcination. The reaction temperature was controlled at 200℃, the heating rate was adjusted to 2℃ / min, and the temperature was maintained for calcination for 3 hours. After the reaction was completed, the copper oxide material was removed.
[0053] (3) The prepared copper oxide material was used as the positive electrode material to assemble a supercapacitor and the electrochemical performance was tested.
[0054] Material characterization testing
[0055] This invention provides SEM images of copper oxide material coated with multi-walled carbon nanotubes prepared by constant current deposition, such as... Figure 2 As shown. Observation Figure 2 It can be clearly observed that multi-walled carbon nanotubes are tightly coated on the surface of copper oxide, which shows that copper oxide material coated with multi-walled carbon nanotubes can be prepared by constant current deposition method.
[0056] Using the uncoated multi-walled carbon nanotube copper oxide obtained in the comparative example as the positive electrode material, after cycle life testing, the negative electrode of the system was characterized by SEM, such as... Figure 3 As shown.
[0057] The copper oxide coated with multi-walled carbon nanotubes prepared in Example 1 was used as the positive electrode of a supercapacitor. After cycle life testing, the negative electrode of the system was characterized by SEM. Figure 4 As shown.
[0058] from Figure 3 and Figure 4 The comparison shows that, Figure 3 The amount of negative electrode deposits in it is significantly higher than that in other parts of the world. Figure 4 The large amount of negative electrode deposition indicates that coating the positive electrode material with multi-walled carbon nanotubes can effectively suppress negative electrode deposition.
[0059] Performance testing
[0060] The materials obtained in Examples 1, 2, 3, 4, and Comparative Example 1 were used as the positive electrodes of supercapacitors, and their electrochemical performance was tested. The capacity retention rates of the supercapacitors in the examples and comparative examples are shown in Table 1.
[0061] Table 1
[0062] Example 1 90.3 Example 2 88.5 Example 3 89.1 Example 4 88.2 Comparative Example 1 73.4
[0063] Table 1 shows that the supercapacitor exhibits the highest capacity retention when the amount of multi-walled carbon nanotubes added is 50 mg. A comparison between Example 1 and Comparative Example 1 demonstrates that coating the cathode material with multi-walled carbon nanotubes can improve the capacity retention of the supercapacitor.
[0064] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a cathode material coated with carbon material for an asymmetric capacitor, characterized in that, The method includes the following steps: 1) The carbon material is placed in concentrated acid for stirring and cleaning, centrifuged, washed with water and alcohol in sequence, and then dried in an oven; the carbon material is one of single-walled carbon nanotubes, multi-walled carbon nanotubes, and graphene. 2) The treated carbon material is added to the electrolyte and mixed; the electrolyte is one of KOH solution or NaOH solution with a concentration of 1~6 mol / L; 3) Using the electrolyte treated in step 2) as the electrodeposition solution, copper foam as the working electrode and platinum sheet as the counter electrode, carbon-coated copper hydroxide is prepared by electrodeposition. The electrodeposition method is constant current deposition. The conditions for constant current deposition are: current of 10~30mA and electrodeposition time of 20~60min. 4) The electrode material obtained in step 3) is placed in a tube furnace for calcination to prepare carbon-coated copper oxide, i.e., the carbon-coated positive electrode material; the calcination temperature is 150~300℃, the calcination time is 2~4h, and the heating rate is 2~5℃ / min.
2. The method for preparing carbon-coated positive electrode material for asymmetric capacitors according to claim 1, characterized in that, The concentrated acid mentioned in step 1) is either concentrated hydrochloric acid or concentrated nitric acid.
3. The method for preparing carbon-coated positive electrode material for asymmetric capacitors according to claim 1, characterized in that, In step 1), the concentrated acid washing and stirring time is 20-60 min; the centrifugation speed is 4000-8000 r / min, and the centrifugation time is 3-8 min.
4. The method for preparing carbon-coated positive electrode material for asymmetric capacitors according to claim 3, characterized in that, In step 1), the concentrated acid washing and stirring time is 30 min; the centrifugation speed is 5000 r / min and the centrifugation time is 5 min.
5. The method for preparing carbon-coated positive electrode material for asymmetric capacitors according to claim 1, characterized in that, In step 2), the electrolyte concentration is 3 mol / L.
6. The method for preparing carbon-coated positive electrode material for asymmetric capacitors according to claim 1, characterized in that, In step 2), the mixing method involves simultaneous stirring and ultrasonic treatment; the stirring and ultrasonic treatment time is 30~60min; and the ultrasonic power is 240~360W.
7. The method for preparing carbon-coated positive electrode material for asymmetric capacitors according to claim 6, characterized in that, The stirring and sonication time was 30 minutes, and the sonication power was 360W.
8. The method for preparing carbon-coated positive electrode material for asymmetric capacitors according to claim 1, characterized in that, Step 3) The calcination temperature of the tube furnace is 200℃; the calcination time is 3h; and the heating rate of the tube furnace is 3℃ / min.
9. A carbon-coated cathode material for an asymmetric capacitor prepared by the method according to any one of claims 1 to 8.
10. An asymmetric capacitor using the carbon material coated with the cathode material as described in claim 9 as the cathode material.
Citation Information
Patent Citations
Preparation and application of cuprous oxide / carbon nanotube / foamy copper composite electrode for heterogeneous electro-Fenton system
CN112408555A
Method of fabricating metal oxide-carbon nanotube composite films using a combined electrochemical deposition and thermal oxidation
KR1020100032012A